Photocatalytic degradation of gaseous toluene over bcc-In2O3 hollow microspheres - Zhang, Q.; Li, Xin Yong; Zhao, Q.; Shi, Y.; Zhang, F.; Liu, B.; Ke, J.; Wang, L. (Elsevier, 2015)
© 2015 Elsevier B.V. All rights reserved. In this work, the body-centered cubic indium oxide (bcc-In2O3) hollow microspheres were prepared via a P123-assisted solvothermal process. The structural properties of samples were investigated by X-ray powder diffraction, scanning electron microscopy, transmission electron microscopy, UV-visible diffusive reflectance spectroscopy, and nitrogen adsorption-desorption isotherms. The photocatalytic effects of degrading gaseous toluene were evaluated by gas chromatography and in situ Fourier transform infrared (FTIR) spectra under a irradiation of a 500 W high pressure xenon lamp. The results indicated that the as-prepared bcc-In2O3 hollow microspheres exhibited a high degradation efficiency towards toluene within a short reaction time. Besides, the preliminary mechanism therein was inferred with the aid of in situ FTIR and electron spin-paramagnetic resonance techniques to understand the degradation process.